The effect of the agricultural mechanization assistance model on socio-economic changes of farmer groups in Palopo city, Indonesia (International Journal of Scientific Research and Management (IJSRM), 2024)
Increasing agricultural productivity through agricultural mechanisation by the Palopo City government of Indonesia is a policy to meet the needs of farmers in developing their agricultural businesses. This study uses innovation and technology adoption variables, variable effectiveness of machinery and agricultural extension as intervening variables to determine effective models to see socio-economic changes in agricultural groups through agricultural mechanisation assistance in Palopo City, Indonesia. This research method used descriptive research techniques with a quantitative analysis approach. Then, all data was collected using a structured questionnaire with closed questions using a Likert scale. The data was tabulated using Microsoft Excel, and then the data collected was analysed by variance-based statistics, namely SEM PLS. According to the study’s SEM analysis findings, 34.6 % of socio-economic changes are influenced by innovation and technology adoption, the impact of agricultural extension workers on socio-economic changes obtained by 4.4 %, while the overall influence of variability on socio-economic changes in community results obtained by 16.6 %.